Nevus unius lateris with bilateral oral mucosal lesions: An unusual presentation - Lovleen Kaur; Bharat B Mahajan; Mohita Mahajan; Shaminder Singh Dhillon (Wolters Kluwer Medknow Publications, 2021)
Verrucous epidermal nevi (VEN) are cutaneous hamartomas characterized by keratinocytic hyperplasia. Majority are linear in distribution and tend to follow the Blaschko lines; however, some may have zosteriform (segmental) or systematized distribution involving widespread areas of skin. The systematized ones are further classified into "Nevus Unius Lateris" when one-half of the body is affected, and "Ichthyosis Hystrix" showing bilateral distribution, both being the uncommon forms. Although it can affect any body part, it rarely involves the head and neck region with seldom involvement of mucosae, scalp, and ear lobes. We saw a 6-year-old child with multiple hyperpigmented verrucous plaques predominantly present over left half of the body, ipsilateral alopecia scalp, and verrucous lesions involving mucosae of palate and tongue, which were present bilaterally. Previously, case reports of oral lesions related to VEN had demonstrated segmental, midline, or unilateral distribution. Hereby, we report this peculiar case of Nevus Unius Lateris with bilateral oral mucosal involvement, owing to its rarity.